Comparing gingival inflammation and salivary acidity to hormonal variation during menstruation - Nahla Kamal Asaad; Hadeel Mohammed Abbood (Elsevier, 2023)
Introduction: Hormonal changes are associated with healthy female in different stages of her life, such as menarche, pregnancy, and menopause. The main female hormones (i.e., Estrogen and progesterone) act as modulators and effectors during different phases of menstrual cycle. Additionally, these hormones were shown to affect the body inflammatory status. Few studies addressed gingivitis and female hormones. Although gingivitis main cause is dental biofilm, female hormones might modulate this inflammation. If no treatment provided, gingivitis might proceed to periodontitis and alveolar bone destruction may appear. The study aim: was to assess the changes in gingival inflammation, and salivary pH in relation to changes in hormonal levels during different menstrual phases in young females. Method: 25 healthy young females with regular menstrual cycles were included. The volunteers were invited to visit the clinic during their 2nd day of menstrual cycle (menses phase (MP)). During the visit, plaque index (PLI) and gingival index (GI) were scored. Additionally, salivary pH was calculated. Follow-up readings were taken on the 20th day of menstruation (pre-menstrual phase (PMP)). The difference in PLI, GI and salivary pH was analysed using t-test and chi-square test. Results: The study showed that PLI and GI increased statistically significantly with increasing levels of female hormones during PMP and decreased during MP (P-value = 0.012 for PLI and 0.0003 for GI). Salivary pH decreases slightly during PMP and saliva becomes more alkaline during MP (P-value = 0.015). Conclusion: The study showed increased gingival inflammation and plaque accumulation during the premenstrual period. It is recommended to raise awareness of gingival inflammation among adult females to prevent progressive changes of periodontitis. However, due to the limited sample size of this study, a comprehensive population-based study is needed to support the findings.